The FT IR and Raman Spectroscopic studies of Some Liquid Crystals - Acimiş, Mahmut; Alaman, Ayşen; AKYÜZ, SEVİM (Taylor and Francis Online, 1993)
Room temperature FT-IR and Raman spectra of some lyotropic liquid crystals in anionic and cationic mesophases composed of sodium dodecylsulphate/ orthophosphoric acid monodecyl ester/H2O and decylammonium chloride/ orthophosphoric acid monodecylester/H2O have been studied together with polarizing microscopy. All the vibrational bands observed are assigned. Intramolecular order is found to decrease upon dilution. Hydrogen bonding type interaction between the head groups of sodium dodecylsulphate or decylammonium chloride and orthophosphoric acid monodecylester is detected.
Keywords: Lyotropic liquid crystals; IR and Raman spectra